Технические аспекты разработки виртуальных лабораторных работ по техническим дисциплинам - Аврунін, О. Г.; Крук, О. Я.; Носова, Т. В.; Семенець, В. В. (Открытое образование, 2008)
Principles for design of virtual laboratory works for technical disciplines are described. Technical aspects of development virtual laboratory works for technical disciplines are proposed.
Keywords: дистанционное обучение; виртуальный лабораторный практикум; технические дисциплины